Avaliação dos centros de atenção psicossocial (Caps) a partir da perspectiva de profissionais - Zanardo, Gabriela Lemos de Pinho (2021)
National and international literature highlights the importance of evaluating and monitoring services and assistance for the qualification of mental health care. In Brazil, different research on qualitative and quantitative approaches has been discussing the advances, limitations and challenges of implementing the psychosocial care model. This study is part of this situation and its general objective was to assess the extent to which the different proposals of the psychiatric reform law and the political guidelines for the functioning of the Psychosocial Care Centers (CAPS) can be implemented in the daily mental health care, from the assessment of CAPS professionals. This is a sequential, qualitative and quantitative mixed method research, operationalized in 2 studies. The first study, of a qualitative character, exploratory and analytical, aimed to analyze the role of CAPS in articulation with different components of the network and its operationalization based on the experience of RAPS professionals in Porto Alegre. Eleven professionals were interviewed and the transcripts of the interviews were submitted to Thematic Analysis, with the help of the Atlas.ti software. Two categories were discussed: 1) the articulation of the CAPS with the Psychosocial Care Network and 2) the articulation of the CAPS with the intersectoral network. The results show that, although specific practices that seek to articulate mental health policy with other sectors occur and that these present promising outcomes, the implementation of the principle of intersectorality remains limited. The second study, of a quantitative character, sought to psychometrically validate the Avalia-CAPS instrument, professional version. A total of 195 professionals, from CAPS from different locations, answered the final version of the instrument with 38 items and the reduced version of SATIS-BR. A Confirmatory Factor Analysis (AFC) of the Avalia-CAPS-P was carried out, testing two models of factor structure, and Convergence Analysis of the two scales. The AFC pointed out satisfactory results with the two models, the single-factor model and the eight-factor model. A third model, which consisted of an adjustment of the eight-factor model, was also presented, in which the four items with the lowest factor loads were excluded. It is noteworthy that the adjusted model presented the best adjustment indexes. The scale as a whole presents adequate reliability indicators (Ωt=0,93 e α=0,92) and the internal consistency of the scale factors varies between α = 0.63 and α = 0.75, with the exception of the family participation, α = 49. In the Convergence analysis, the dimensions of the Avalia-CAPS-P correlate significantly and moderately with the global assessment and the SATIS-BR dimensions. It was found that the Avalia-CAPS-P instrument has significant indexes of validity and can assist in assessing the quality of services. The results of the studies are complementary in understanding this field, since the data referring to the difficulties encountered by professionals in comprehensive care and in the intersectoral articulation of the CAPS with other devices, helps to deepen the analysis of the results of the respective factors of the validated scale. The importance of developing new studies is highlighted, aiming to compare the assessment of the different actors in this field, for a better understanding, monitoring and effectiveness of quality psychosocial care.